Food system sustainability for health and well-being of Indigenous Peoples - Kuhnlein, Harriet V (Public health nutrition, 2015)
To describe how Indigenous Peoples understand how to enhance use of their food systems to promote sustainability, as demonstrated in several food-based interventions. Comments contributed by partners from case studies of Indigenous Peoples and their food systems attending an international meeting were implemented with public health interventions at the community level in nine countries. The Rockefeller Foundation Bellagio Conference Center in Bellagio, Italy, where experiences from case studies of Indigenous Peoples were considered and then conducted in their home communities in rural areas. Leaders of the Indigenous Peoples' case studies, their communities and their academic partners. Reported strategies on how to improve use of local food systems in case study communities of Indigenous Peoples. Indigenous Peoples' reflections on their local food systems should be encouraged and acted upon to protect and promote sustainability of the cultures and ecosystems that derive their food systems. Promoting use of local traditional food biodiversity is an essential driver of food system sustainability for Indigenous Peoples, and contributes to global consciousness for protecting food biodiversity and food system sustainability more broadly. Key lessons learned, key messages and good practices for nutrition and public health practitioners and policy makers are given.